2007
DOI: 10.1017/s0265021507000178
|View full text |Cite
|
Sign up to set email alerts
|

Levobupivacaine hydrochloride and sufentanil have no antimicrobial effect at 25°C in vitro

Abstract: Phrenic nerve infiltration with ropivacaine 0.2% 10 mL reduced the incidence and delayed the onset of ipsilateral shoulder pain during the first 24 h after open lung resection, with no clinically relevant effects on respiratory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
2
14
0
1
Order By: Relevance
“…Hodson et al reported in their study that the antibacterial effects of bupivacaine are higher than that of the levobupivacaine [19]. In another study the authors worked on the combined antibacterial effects of levobupivacaine and sufentanil and found that these two drugs can be used safely in regional anesthesia without any bacterial reproduction at room temperature [20]. We did not encounter any sign of macroscopic infection on the wounds and these results correlate with the prior studies done by other authors.…”
Section: Discussionsupporting
confidence: 87%
“…Hodson et al reported in their study that the antibacterial effects of bupivacaine are higher than that of the levobupivacaine [19]. In another study the authors worked on the combined antibacterial effects of levobupivacaine and sufentanil and found that these two drugs can be used safely in regional anesthesia without any bacterial reproduction at room temperature [20]. We did not encounter any sign of macroscopic infection on the wounds and these results correlate with the prior studies done by other authors.…”
Section: Discussionsupporting
confidence: 87%
“…Since then, interest in the antimicrobial activities of local anaesthetics have spread to clinical disciplines as diverse as dentistry (33), anaesthetics (34)(35)(36)(37)(38)(39)(40)(41)(42), otorhinolaryngology (43), pulmonology (44) and ophthalmology (45,46).…”
Section: Past Investigations Into the Antimicrobial Activity Of Bupivmentioning
confidence: 99%
“…In contrast to this, however, an in-use clinical study found that morphine and pethidine prepared for titration for individual patients have a high rate of contamination during clinical use (64). There is some evidence that sufentanil may have some synergistic antimicrobial activity when used in combination with bupivacaine (48), although another study found sufentanil to neither inhibit nor encourage microbial growth (40). Tamanai-Shacoori suggests that this non-specific antimicrobial activity of At concentrations of 5mg/ml, pethidine inhibited 6 of 10 organisms.…”
Section: Microbial Contamination Of Opioids In Generalmentioning
confidence: 99%
“…Even, one study reported a prevalence of up to 97% [9]. ISP could impair effective breathing and the effectiveness of physical therapy in the early postoperative period [14].…”
Section: Frequency and Importancementioning
confidence: 99%
“…ISP onset could be as early as the first postoperative hour [9, 11]. With treatment, the pain severity will decrease over the first 4 to 6 hours [5, 11, 13].…”
Section: Pain Characteristicsmentioning
confidence: 99%